Electrochemical Characterization of Copper Coatings on Low Carbon Steel from Industrial Waste (2013)
In the present investigation was obtained electro-copper coating on steel AISI SAE 1020, electrolyte was used as an industrial waste obtained from the stripping of copper. The current densities were 2.5 A/dm2 , 5 A/dm2 y 7.5 A/dm2 and concentration of 222 g / l of copper sulfate (CuSO4). The corrosion behavior of the substrate and the coatings obtained were studied by electrochemical impedance spectroscopy and potentiodynamic polarization curves. Additionally, we examined the surfaces of the coatings by scanning electron microscopy (SEM). The study shows that these coatings comply with the standards for use as ground poles.